Pengaruh Faktor Keuangan dan Non Keuangan Terhadap Nilai Underpricing pada Perusahaan yang Melakukan Initial Public Offering (Studi Pada Perusahaan yang Listing di Bursa Efek Indonesia Tahun 2009-2012) - Rangga Radipria; Meina Wulansari Yusniar; Asrid Juniar (Universitas Lambung Mangkurat, 2015)
Underpricing is a result of uncertainty of the stock price on the primary market which occurs because of the asymmetry information which is owned by the parties involved in the initial public offering, namely issuers, underwriters, and public investors. This study was conducted to determine how and whether the current ratio, return on assets, debt equity ratio, earnings per share, the size of the company, the size of the stock offering, the age of the company, underwriter reputation, and the reputation of Auditors have any influence on underpricing on companies doing IPOs on the Stock Exchange year 2009-2012. The type of this study was descriptive verification with causality. The population in this study was companies listed on the Indonesia Stock Exchange (IDX) year 2009-2012 with samples of 64 companies which selected by using purposive sampling method. The type of data collected and used in this research were secondary data collected through documentation and literature studies. Method of data analysis used was multiple linear regression which have fulfilled classical assumption test. The results showed that the underwriter reputation variables have affected the underpricing. The results of multiple regression analysis showed that the coefficient of determination Adjusted R2 = 17.6%, which means that all independent variables could explain the variation of the dependent variable, namely the underpricing of 17.6%.